Application of empirical mode decomposition in improving group method of data handling - Razif, Nur Rafiqah Abdul; Shabri, Ani (2023)
The accuracy of electricity load demand forecasting is essential for avoiding energy waste and overuse. Hence, this paper aims to model the forecast electricity load demand by combining Empirical Mode Decomposition (EMD) with Group Method of Data Handling (GMDH) model. The proposed methodology works in three steps: it decomposes the original load data series into several Intrinsic Model Functions (IMFs) and one residual component, enables individual forecasting of each IMF and the residual using the GMDH model by using the Partial Autocorrelation Function (PACF) as the input variable, and aggregates all the forecasted values to yield the final prediction for electricity load demand. To compare the performance, another model is considered namely the combination of EMD with the Artificial Neural Network (EMD-ANN). The empirical result from the performance evaluation concluded that EMD-GMDH outperforms the EMD-ANN as well as the GMDH model without decomposing the time series.